Exploring Numerical Competence: Analysis Of Students' Mathematical Representation Skills in PISA Space and Shape Content - Febriyani, Ajda Audita; Setyaningsih, Nining (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to analyze students' mathematical representation skills in solving PISA Space and Shape content questions, taking into account their numerical ab. Mathematical representation is a key skills in understanding and solving mathematical problems, while numerical skills play a vital role in developing an understanding of concepts and their applications in spatial and shape contexts.The research method employed is a qualitative approach, collecting data from students through written tests and interviews. The research instruments include questions reflecting Space and Shape content from PISA, as well as numerical skills tests.The research findings indicate a significant relationship between students' numerical skills and their skills to represent mathematical problems related to Space and Shape. Students with better numerical skills tend to have better mathematical representation skills. Furthermore, these findings can provide insights for educators and researchers to develop teaching strategies that integrate the development of numerical skills and mathematical representation, there by enhancing the quality of students' mathematical understanding at a global level.